Decoding Cancel Culture Representation: A Semiotic Content Analysis of Korean Movies and Series - Ditha Amira Natania; Kusuma, Rina Sari (Jogjakarta Communication Conference (JCC), 2025)
Cancel culture is a collective practice where individuals hold public figures accountable for actions or statements that violate social, cultural, ethical, or moral norms. In South Korea, this phenomenon has been long ingrained, amplified by active social media use and the spread of the Korean Wave (Hallyu) through K-pop, films, and dramas. The entertainment industry serves as a lens to explore how Korean society enforces ethical values, particularly through cancel culture. This study examines how cancel culture is portrayed in selected Korean films and dramas. Using a constructivist paradigm and a qualitative approach, the research applies Roland Barthes' semiotic analysis (denotation, connotation, and myth) to identify its representation. Findings reveal that the media significantly shapes public perception. Characters affected by cancel culture face severe personal and professional consequences, although rehabilitation depends on societal acceptance. Reflecting the reality of cancel culture in Korean society finds the involvement of influencers or public figures who are involved in scandals/rumors as the cause, resulting in negative comments and social condemnation that leads to career loss or social exclusion.